Power System Assessment for the Burnt Mountain Seismic Observatory - Lamp, Thomas R., Jr. (1994)
A team of scientists and engineers of the US Air Forces' Wright Laboratory conducted a study of electrical power technologies for use by the Air Force in operating a seismic observatory on Burnt Mountain in the Alaskan Interior. This assessment evaluated a number of proven candidate power generation technologies; including, radioisotope and propane-fueled thermoelectric generators (RTGs and TEGs) , engine and wind-driven mechanical generators, chemical storage batteries, fuel cells, photovoltaics, and electrical transmission lines from Fort Yukon to Burnt Mountain. After initial evaluations were completed, the study focused on the most promising technologies, thermoelectric generators (RTGs and TEGs) and photovoltaic generators (PV). Several power systems based on emerging-technologies were also evaluated; to include, thermionic, thermal photovoltaic, Stirling, alkali metal thermoelectric converters (AMTEC), and hydrogen thermoelectric converters (HYTEC).